Communication and market sharing: An experiment on the exchange of soft and hard information - Andreas Freitag; Catherine Roux; Christian Thöni (University of Basel, Center of Business and Economics (WWZ), 2019)
We study the role of communication in collusive market sharing. In a series of Cournot oligopoly experiments with multiple markets and repeated interaction, we vary the types of information that firms can exchange. We distinguish between hard information-verifiable information about past conduct-and soft information- unbinding information about future conduct. We find that the effect of communication on the firms' ability to collude depends on the type of information available: market prices increase only slightly when hard information allows perfect monitoring of rivals' past actions, but the price raise due to soft information, however, is substantial. The explicit consent of each cartel member to a common collusive strategy, even if stated only once, drives this strong effect. Our results point to the types and contents of communication that should be of particular concern to antitrust authorities.
Keywords: C91; L13; L41; 330; Collusion; Market Sharing; Cournot Oligopoly; Information; Communication; Experiments